For the right to a sustainable city: a proposed Linear Park for Feira de Santana, Bahia - Vitória, Tayná de Oliveira; Santos , Rosângela Leal; Chaves, Joselisa Maria (Technical and Scientific Journal Green Cities, 2025)
Objective – To demonstrate the socio-environmental situation of the city of Feira de Santana, Bahia, using data from the Sustainable Development Index for Cities (SDCI), with a view to implementing a Linear Park on the terraces of the Olhos D'Água River parallel to Macário Cerqueira Avenue.Methodology – This work is classified as qualitative-quantitative due to its approach, as it uses both qualitative and quantitative data. Due to its nature, it is classified as applied research, as it seeks to generate knowledge for practical application in solving specific problems. In this case, the proposed implementation of the Linear Park is a solution to address the socio-environmental problems present in the Olhos D'Água watershed and adjacent neighborhoods, which also generates reductions in the sustainability level of the city of Feira de Santana.Originality/Relevance – The relevance of this work is justified by the studies and research of Carelli (2011), Vitória and Vieira (2022) and Vitória and Vieira (2023), in which urban-environmental changes were identified in the Olhos D'Água River basin, in the city of Feira de Santana, which makes the implementation of a Linear Park on the river terraces contribute to its revitalization, as well as for the river and vegetation to provide their ecosystem services to the population, mainly the capture of rainwater and the reduction of flooding in the neighborhoods of the basin; as well as the reduction of the effect known as "heat islands". In addition, with the implementation of a Linear Park, a space for leisure, social gatherings and environmental education will be created, with landscape and tourism benefits, which can boost the local economy.Results – It was found that Feira de Santana has a low level of Sustainable Development, with an overall score of 47.32 out of 100. A relevant investment to improve the situation of Feira de Santana in terms of the treatment of natural resources is the implementation of the Linear Park, a protected, predominantly linear urban infrastructure in which waterways are predominant elements, which will allow vegetation and water resources to provide their ecosystem services to the population.Theoretical/Methodological Contributions – This work reaffirms the view that urban space should not be planned solely for circulation and construction, but as a geosystem where urban rivers, permanent conservation areas, and the population coexist. Another theoretical contribution is the adoption of the urban landscape as a structuring element of the project, not as an environment, but as a product of the relationship between society and nature. Furthermore, this study promotes the theorization of "linear park" green infrastructure as a nature-based solution (NBS) and as essential urban infrastructure in the face of the climate crisis, interconnecting drainage, shading, microclimate, and recreation.Social and Environmental Contributions – The proposed modeling, although preliminary, already shows potential improvements for the designated area, which will be enjoyed by the population of the neighborhoods adjacent to the Olhos D’Água basin, as well as by the entire population of Feira de Santana, which lacks public leisure spaces and facilities linked to water resources—which are abundant in Feira de Santana—yet are not revitalized or designed with socio-environmental purposes. Furthermore, linear parks play a fundamental role in urban climate adaptation, as they promote urban revegetation, which in turn provides natural shading, reduces surface temperatures, and improves the microclimate in areas previously exposed to sunlight and waterlogging; all of which reduces urban heat islands.
Keywords: Urban sustainability; Greenways; 2030 Agenda